2006
DOI: 10.1017/s0266467406003452
|View full text |Cite
|
Sign up to set email alerts
|

Community dynamics during early secondary succession in Mexican tropical rain forests

Abstract: Stand structure dynamics during early secondary forest succession were related to mortality, growth and recruitment rates, and the dependence of these demographic processes on fallow age and initial stand structure attributes was evaluated. In 11 secondary tropical rain-forest sites (1.5-19 y) in Chiapas, Mexico, one plot of 10 × 50 m was established. Diameter and height were measured for all trees ≥ 1 cm dbh, and their survival, growth and recruitment was monitored over a 2-y period. Changes in stand structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
137
3
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 50 publications
9
137
3
7
Order By: Relevance
“…Principally, it has been suggested that previously reported net biomass increases 4 could be driven by recovery of forests from local disturbances 11 . However, contrary to observations from recovering neotropical forests 13 and successional studies 14 , the plots have collectively experienced increased biomass growth ( Fig. 1), accelerated stem recruitment and death (Extended Data Fig.…”
contrasting
confidence: 76%
“…Principally, it has been suggested that previously reported net biomass increases 4 could be driven by recovery of forests from local disturbances 11 . However, contrary to observations from recovering neotropical forests 13 and successional studies 14 , the plots have collectively experienced increased biomass growth ( Fig. 1), accelerated stem recruitment and death (Extended Data Fig.…”
contrasting
confidence: 76%
“…As a result, most of our knowledge on forest succession is based on chronosequences (13), a space-for-time substitution approach that assumes that succession follows a single, largely deterministic trajectory over time. Recent studies, however, have shown that successional pathways vary widely, even among neighboring stands with similar environmental conditions and disturbance history (14)(15)(16)(17)(18). In the case of posthurricane succession in Nicaragua, such variation has been attributed to stochastic processes associated with nonequilibrium community dynamics (18).…”
mentioning
confidence: 99%
“…These metrics, however, are likely to change interdependently during succession. In particular, successional changes in stem density are associated with changes in basal area, and vice versa (9,17). Yet, other possible Significance Although forest succession has been approached as a predictable process, successional trajectories vary widely, even among nearby stands with similar environmental conditions and disturbance histories.…”
mentioning
confidence: 99%
“…2014). In general, forests at early stages are in the process of accumulating biomass rapidly (Van Breugel, Martínez‐Ramos, & Bongers, 2006). As the vegetation develops, taller longer‐lived plant species in late successional stages progressively replace the species which are faster‐growing, having higher mortality, recruitment, stem density, and lower basal area (Garnier et al., 2004).…”
Section: Discussionmentioning
confidence: 99%